DEPTH TO BASEMENT ESTIMATION AND BASEMENT TOPOGRAPHIC MAPPING FROM AEROMAGNETIC DATA ACQUIRED OVER THE CENTRAL PART OF THE BORNO BASIN, NORTHEASTERN NIGERIA; IMPLICATIONS FOR PETROLEUM EXPLORATION - Abdulmumin, Yusuf; Jibrin, Abdulmajid Isa; Saidu, Fatima; Kariya, Idris Ismail; Yusuf, Jamaluddeen (FUDMA JOURNAL OF SCIENCES, 2024)
A reconnaissance for petroleum exploration was conducted in the central part of the Nigerian sector of the Chad Basin (Borno Basin) using High Resolution Aeromagnetic Data (HRAM) obtained from the Nigerian Geological Survey Agency (NGSA). The study was aimed at identifying high-prospect areas by estimating sedimentary thickness and mapping basement geometry. Upward continuation eliminated shallow magnetic sources, making it easier to focus on deeper regional geologic structures thought to have originated from the basement. To make the anomalies easier to interpret, the reduction to equator processing approach was employed to concentrate them on the associated geologic causes. At various solution positions, the depth to basement rocks was calculated using a new 3D Located Euler Deconvolution depth weighting method. The rocks in the study area have residual magnetic intensities ranging from -275 to 190 nT. The basement topography exhibits undulations and thicknesses varying from around 100 m to over 3 km, as indicated by the results of the Euler Deconvolution and the basement topographic map. Four major sub-basins, situated in the southern and northeastern parts of the study area, with thicknesses ranging from > 2.5 to up to 3 km, with the largest sub-basin, situated in the southern portion of the study area, having the highest thickness, up to 3.4 km in certain areas. These sub-basins are thick enough to generate geothermal gradient for organic matter maturation where the right source rock exist hence recommendable for further geophysical investigation using reflection seismic and other petrophysical studies.